POSISI DAN JARAK KONSTITUEN ANTARA UNSUR TERSULIH DAN PENYULIH DALAM NOVEL âEMPRIT ABUNTUT BEDHUGâ KARYA SUPARTO BRATA - Indrayanto, Bayu (MAGISTRA, 2016)
This research is a descriptive qualitative research attempting at describing : the position andconstituent duration between substituted aspect and substitutor of âEmprit Abuntut Bedhugâ novel written bySuparto Brata. The research data are Javanesse narrative discourse which its substitution aspect located in thediscource former sentences. The data obtained from the written sourceâseries novels of Detective HandakaEAB written by Suparto Brata. Conclusion is the substitution of EAB novel is mostly substituted constituentstanding as either anaphoric or even cataphoric or both. Mean while, the duration between the constituent andthe substituted aspect with the substitutor constituent are sometimes narrows and remote. Its narrow andremote duration between substitutor and substituted aspect can be viewed in the sentences of one paragraph,among sentences in one paragraph, and sentences of the paragraphs.Keywords :Substitution,substituted constituent, substitutor